Hunter syndrome with hyperthyroidism: a 16 month follow-up reprt - Din Alfina; Endy Paryanto Prawirohartono; Roni Naning; Neti Nurani (Indonesian Pediatric Society, 2018)
Mucopolysaccharidosis (MPS) is a rare genetic disorder caused by a deficiency in the activity of lysosomal enzymes required for glycosaminoglycan (GAG) degradation. An accumulation of GAG in many organs results in progressive cellular damage, and clinically results in joint stiffness, airway and cardiac as well as, mental and hearing impairments. Incidence of MPS was reportedly 2.04 per 100,000 live births, but varies depending on type and region. In Taiwan, MPS type II was the most prevalent MPS, with an incidence of 1.07 per 100,000 live births.1 MPS is generally inherited in an autosomal recessive pattern, with the exception of MPS II, which is X-linked recessive.2 There are seven types of MPS (MPS I, II, III, IV, VI, VII, and IX), based on enzyme deficits.3 The types of MPS with their enzyme deficiencies are listed in Table 1. Mucopolysaccharidosis shows wide clinical heterogenity, and is, therefore, difficult to diagnose. Skeletal involvement in MPS include coarse face, loss of joint range of motion, restricted mobility, and slowed growth leading to short stature. Other signs and symptoms include vision and hearing loss, recurrent respiratory infections, obstructive sleep apnea, hepatosplenomegaly, umbilical and inguinal hernia, hydrocephalus, spinal cord compression, and cognitive impairment.2,4 Patients with suspected MPS should have urinary GAG laboratory testing and enzyme activity assays in tissue (blood or fibroblasts). Urinary elevation of GAG, as compared with GAG levels expected in age-matched normal subjects, is the first diagnostic approach. The definitive specific diagnosis for MPS is based on enzyme activity assays from cultured fibroblasts, leukocytes, plasma, or serum.2,5,6 The MPS patients require multidiciplinary subspeciality management, including ENT, orthopedics, cardiology, pulmonary, growth and development, and physiotherapy. Specific treatments for MPS are hematopoietic stem cell transplantation (HSCT) and enzyme-replacement therapy (ERT) with recombinant human enzymes for MPS I, II, and VI.3,6,7,8 Life expectancies in MPS may vary among types, but generally are markedly reduced. Patients with MPS III and VII and severe forms of MPS I and MPS II have mental retardation. Patients with MPS II usually survive until only the second decade of life, with respiratory failure as the leading cause of death (56%), followed by cardiac failure (18%).9,10